Does parental monitoring moderate the relationship between bullying and adolescent nonsuicidal self-injury and suicidal behavior?: a community-based self-report study of adolescents in Germany - Jantzer, Vanessa; Haffner, Johann; Parzer, Peter; Resch, Franz; Kaess, Michael (BMC public health, 2015)
Being a victim of bullying in school is clearly linked to various social, emotional, and behavioral problems including self-harm behavior. However, it is not known whether even occasional victimization has similar negative consequences and whether protective factors such as social support may prevent those harmful developments. The present study therefore focuses on the nonsuicidal self-injury (NSSI) and suicidal behavior (SB) in victims of bullying and the potentially moderating effect of parental monitoring.